Serayu Asri Program as a Social Innovation-Based Systemic Change for the Empowerment of Women Farmers - Budiarto, Condro; Ikhsan, M. Amin; Utami, Matahun Triastuti Budi; Putri, Fadilla Windra (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
This research describes how women establish their bargaining position in efforts to challenge societal values regarding the division of roles between women and men by participating in community empowerment initiatives conducted under the Corporate Social Responsibility (CSR) framework of PT PLN Indonesia Power UBP Mrica PLTA PB Soedirman. The research used a qualitative method to analyze the process of social innovation in community empowerment, explaining several stages leading to systemic changes that impact ecosystem conservation. The findings revealed that the social innovation program initiated by the company within the framework of community empowerment is effective in blending the roles of women and men in agriculture. It enhances the bargaining power of women to take on strategic roles within organizational structures, effectively strengthens groups, improves individual quality, and facilitates systemic changes that positively impact ecosystem conservation.